2017
DOI: 10.31235/osf.io/gux3h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using WhatsApp in EFL Instruction with Saudi Arabian University Students

Abstract: Messaging tools such as SMS are effective tools for foreign language learning. While many quasi-experimental studies confirm efficacy and positive student attitudes towards these types of tools, little is known about existing teaching practices that utilize messaging tools in tertiary contexts, or the attitudes of students or instructors towards them. This qualitative study investigates the use of WhatsApp, one popular messaging application, in teaching English as a Foreign Language (EFL) through examining the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some studies conducted by some researchers about utilizing WhatsApp in English language learning. Alsaleem (2013) examined the effect of the use of WhatsApp on English as Foreign Language (EFL) students in written vocabulary tasks in Saudi Arabia. The author found that WhatsApp had a positive effect on students' performances.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies conducted by some researchers about utilizing WhatsApp in English language learning. Alsaleem (2013) examined the effect of the use of WhatsApp on English as Foreign Language (EFL) students in written vocabulary tasks in Saudi Arabia. The author found that WhatsApp had a positive effect on students' performances.…”
Section: Introductionmentioning
confidence: 99%